2018
DOI: 10.3233/jad-180353
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Burden and Risk of Stroke and Death in People with Different Types of Dementia

Abstract: The use of anticholinergic medicines may be associated with an increased risk of stroke and death in people with dementia. A dose-response relationship was observed. Careful consideration should be made when prescribing medications with anticholinergic properties to people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
2
30
2
Order By: Relevance
“…Our cox proportional hazard models showed that higher anticholinergic burden was associated with higher mortality rates among people with dementia in our cohort. Similar to past studies assessing mortality rates in dementia, we also noted that being of male gender and increased age significantly increases mortality rates (Tan et al, 2018;Garcia-Ptacek et al, 2014;. On the other hand, being married and living in some of the least deprived areas, significantly decreased mortality (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…Our cox proportional hazard models showed that higher anticholinergic burden was associated with higher mortality rates among people with dementia in our cohort. Similar to past studies assessing mortality rates in dementia, we also noted that being of male gender and increased age significantly increases mortality rates (Tan et al, 2018;Garcia-Ptacek et al, 2014;. On the other hand, being married and living in some of the least deprived areas, significantly decreased mortality (Table 3).…”
Section: Discussionsupporting
confidence: 88%
“…ChEIs have been proven to have symptomatic effects in Alzheimer´s dementia beyond those detected by standard measures of cognition. As previously shown by our group, ChEIs have been associated with reductions in myocardial infarction 28 , stroke 27 and mortality 27 , while anticholinergic medications have been associated with increases in stroke and mortality risk 40 .…”
Section: Discussionsupporting
confidence: 54%
“…Anticholinergics have also been found to be associated with higher mortality in institutionalized elderly, especially in those with coronary disease (Vetrano et al, 2016) due to the greater vulnerability to the proarrhythmic effects of these drugs. A longitudinal study found a dose-dependent association between taking anticholinergics and the risk of stroke and death in elderly people with Alzheimer’s disease, mixed dementia and vascular dementia (Tan et al, 2018) which would parallel to the well-known risk of antipsychotics. Nevertheless, this risk does not seem to be directly associated to the possible anticholinergic effect of antipsychotics, since it is very different among the different drugs (Maust et al, 2015).…”
Section: Discussionmentioning
confidence: 99%